2017
DOI: 10.18282/amor.v3.is1.211
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-associated infections among patients with different types of acute leukemia in China: A surveillance-based study

Abstract: Healthcare-associated infections (HAIs) may be diverse among patients with acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL). However studies were limited. We aimed to quantify and compare the characteristics and relevant factors associated with HAIs among patients with AML and ALL. The surveillance-based study was conducted in a university teaching hospital. All adult patients diagnosed with acute leukemia (AL) and admitted into the Hematology Department for over 48 h were included. HAI char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…19 In lymphoid neoplasms, fewer mature T/NK and B-cells, and a reduced adaptive immune-response are usually observed, however the innate system remains relatively intact to protect against HAIs. 13 HAIs were mostly clinically documented in our study; this is in line with some other studies. 12,20,21 This could be explained by the fact that doctors prefer early empirical therapy over microbiological confirmation of infections.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…19 In lymphoid neoplasms, fewer mature T/NK and B-cells, and a reduced adaptive immune-response are usually observed, however the innate system remains relatively intact to protect against HAIs. 13 HAIs were mostly clinically documented in our study; this is in line with some other studies. 12,20,21 This could be explained by the fact that doctors prefer early empirical therapy over microbiological confirmation of infections.…”
Section: Discussionsupporting
confidence: 93%
“…Neutropenia was revealed as a risk factor of HAIs in our study, this goes hand in hand with Hui liu et al 13 and Biswal et al 17 who found that neutropenia increases risk of nosocomial infections in haematology ward. Previous studies have demonstrated that neutropenia usually occurs during the first course of induction chemotherapy 17 and this increases the risk of infections among patients undertaking induction chemotherapy.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations